Halal Concept Hotels From The Perspective of Domestic and Foreign Customers: Content Analysis of Positive and Negative Reviews - Özkan, Bekir (My University, 2025)
The purpose of this study is to evaluate the positive and negative online reviews made by domestic and foreign customers who stayed at halal concept hotels. For this purpose, 29,059 reviews were collected for 15 hotels selected from halalbooking.com. Python coding was used to extract the reviews. All reviews were collected in May 2025. Voyant-Tools was used to analyze the reviews. The research results indicate that positive reviews largely concern cleanliness, family-friendly facilities, the availability of separate halal-compliant areas, and the helpfulness of the staff. Conversely, negative reviews stem from issues such as poor hygiene, the uniformity and poor quality of food, the unprofessional attitude of staff, inadequate infrastructure, and the discrepancy between price and perceived value. Domestic customers particularly value value for money, family-oriented services, and child-friendly amenities, while also being more sensitive to hygiene and food variety. Domestic customers generally expressed negative feedback, including poor room cleanliness, limited entertainment options, and an imbalance between cost and service quality. Positive reviews from foreign customers frequently emphasized the welcoming staff, food variety, and spa services. Negative feedback from foreign customers focused on staff's poor communication skills in English and other languages, the lack of consistent implementation of halal standards, noise, lack of room maintenance, and high prices. The research results indicate significant practical and managerial implications for halal concept hotels.
Keywords: Customer reviews; Halal consept hotel; Positive reviews; Negative reviews